Mamluk carpets - El-Gammal, Ramza (AUC Knowledge Fountain, 2012)
"The subject matter of this thesis will be the Mamluk rugs of Egypt. What is meant by this are the geometric carpets that are thought to have been manufactured in Egypt under Mamluk rule as well as those in the same style that were manufactured during the first few decades of Ottoman rule".